INTEGRATION OF UAV AND ANTI-UAV SYSTEMS IN STATE BORDER PROTECTION: INTERNATIONAL EXPERIENCE AND MODERN APPROACHES (Eureka Journal of Artificial Intelligence and Data Innovation, 2026)
This article examines the role of Unmanned Aerial Vehicles (UAVs) in 21st-century border conflicts and hybrid warfare, highlighting their tactical and strategic advantages as well as the emerging threats they pose to national security. Drawing on the insights and experiences from recent conflicts, such as the Russia-Ukraine war and the Nagorno-Karabakh conflict, the study analyzes how the evolution of drone technology is fundamentally reshaping border defense and protection frameworks.
Keywords: Unmanned Aerial Vehicles (UAV), border security, asymmetric warfare, FPV drones, cyber threats, Electronic Warfare (EW), military logistics, “Smart Border”, anti-UAV.